2014
DOI: 10.1586/1744666x.2014.949674
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D: a new player in kidney transplantation?

Abstract: Vitamin D is a hormone with pleiotropic effects. It mainly regulates calcium and phosphate metabolism through interactions with FGF23 and its receptor klotho. In addition, it has been shown that Vitamin D also regulates the immune response and has protective effects from cardiovascular disease, cancer and infections. Most renal transplant recipients have overt Vitamin D deficiency, a condition that may be associated with a decline in graft function and other complications. After kidney transplantation, elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 79 publications
2
12
1
Order By: Relevance
“… 50 Furthermore, the use of corticosteroids contributes to low serum levels of 25(OH) vitamin D. 51 Hence, vitamin D prophylaxis might be more effective in patients on long-term steroid therapy; however, the risk of associated hypercalcemia and hypercalciuria through excessive calcium and vitamin D supplementations should also be considered. 52 …”
Section: Discussionmentioning
confidence: 99%
“… 50 Furthermore, the use of corticosteroids contributes to low serum levels of 25(OH) vitamin D. 51 Hence, vitamin D prophylaxis might be more effective in patients on long-term steroid therapy; however, the risk of associated hypercalcemia and hypercalciuria through excessive calcium and vitamin D supplementations should also be considered. 52 …”
Section: Discussionmentioning
confidence: 99%
“…The beneficial therapeutic effects of VitD and VitD analogues have been proposed in many conditions, ranging from proteinuria, fibrosis, atherosclerosis and inflammation to cancer therapy28293031323341. It has been found that VDR regulates at least 229 genes through binding to 2776 genomic DNA binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, no data have been reported on the potential effects of VitD on lymphatic endothelial cells (LECs) and lymphangiogenesis. The impact of VitD and its analogues on renal pathophysiology has been extensively studied282930313233. Most of the results from these studies suggest that VitD may be considered a generally safe and effective therapeutic in diverse kidney diseases, but the effect of VitD on renal lymphatics and lymphangiogenesis has not yet been described.…”
mentioning
confidence: 99%
“…Studies with active vitamin D analogs have reported the prevention of bone loss at the femoral and lumbar regions, but have not been sufficiently powered to determine fracture outcomes [ 73 , 95 ]. The risk of associated hypercalcemia and hypercalciuria with excessive calcium and vitamin D supplementations should also be considered [ 96 ]. Some authors consider prophylactic therapies with anti-resorptive medications for patients with osteopenia and a high risk of fracture.…”
Section: Managementmentioning
confidence: 99%